Carreira ilustrada, ciência química e ações higienistas: a trajetória de José Vieira de Faria Aragão Ataliba, Portugal-Coimbra, Brasil-Salvador (1820-1853) - Silva, Ana Lícia de Melo (2014)
This study is base don the process of illustration by José Vieira de Faria Aragão Ataliba (1804- 1853). I have made such a choice because this person used to be a chemistry professor at the medical school in Bahia from 1833 to 1837. This way, considering the activitie shehad, I proposed three main goals. First, tok now how his process was developed in Portugal as still a student at the Coimbra University; second, tounder stand his major in general, as well as his experiences in that country and, third, to get to know his path towards this carrer, identifying chemistry as an interface in his hygene activities. This part of theres earch starts back in 1820, when José Vieira Ataliba entered the university. It finishes in 1853, due to his death. This investigation is a result of various earches in files and libraries in Salvador, Coimbra and Lisbon, be sides reading lots of news papers. The registers, built essencially through news papers, school record sandh is memoirs, were, unfortunately, fragmented and not cronological. Despite this, all the information all owed us to see how certain cultural habits have been acquired by him. His cultural experience has conducted us to reflect about the medical study plans from 1772 to 1812, the theoretical debates on the chemistry teachin gat that university, and also the illustration process in Portugal. Through all these postulations, it has been possible tounder stant José Vieira Ataliba’s professional attitude, when executing hygeneactions in Bahia, based in chemical pretexts.